KRITERIA BUKU AJAR BAHASA ARAB DALAM KITAB IDHA`AT - Aris Junaedi Abdilah; Maman Abdurrahman (Institut Agama Islam Darusssalam Blokagung, 2023)
This research aims to determine the criteria for a good Arabic language textbook according to Sheikh Fauzan in the book